On the acquisition of statives in child Russian - Brun, Dina; Babyonyshev, Maria (ZAS Papers in Linguistics, 2003)
It has been previously reported that in languages demonstrating the Root Infinitive (RI) Stage the use of RIs is characterized by two properties: these forms are overwhelmingly eventive and have, in the majority of instances, a modal interpretation. Hoekstra and Hyams (1998, 1999) have proposed a theory stating that these two properties of RIs are co-dependent in that the application of the modal reference restriction limits the use of the aspectual verbal classes to eventive predicates. Furthermore, this theory assumed that the described mutual dependency of these constraints was valid cross-linguistically. In this paper, we investigate the application of this theory to the case of RIs in Russian, one of the languages exhibiting the RI Stage. Using new longitudinal data from two monolingual Russian-speaking children, we demonstrate that the predictions of Hoekstra and Hyams’ approach are not realized for Russian child speech. While the constraint requiring that Ris have a modal reference does not seem to apply in Russian since the infinitival forms do receive past and present tense interpretation, these predicates are still overwhelmingly eventive and stative predicates appear mostly as finite verbs. Having shown that a theory connecting the application of the two restrictions on RIs does not account for the Russian data, we examine several alternative analyses of Russian RIs. We arrive at a conclusion that an explanation based on the lack of the event variable in stative predicates (Kratzer 1989) necessary for the interpretation of RIs in discourse (Avrutin 1997) succeeds in handling the Russian data presented in this article.